Meritokrasi, Populisme Kanan, dan Revitalisasi Diskursus Publik: Perspektif Filosofis Michael Sandel - Tan, Petrus (Fakultas Teologi, Universitas Sanata Dharma, 2024)
This article aims to elaborate the phenomenon of right-wing populism based on the thought of Michael Sandel on the tyranny of meritocracy. Various previous literatures understand right-wing populism as an anti-pluralism and anti-globalization movement. However, these analyses fail to see that meritocracy has fueled the anger of working class and the losers as expressed in the populist movement. This study uses literature review and critical analysis methods. This study indicates that: 1) Meritocracy is a certain moral belief in individual success that justifies inequality as fair based on the basic principles of liberalism; 2) There are five key theses on meritocracy that trigger right-wing populism, namely: a person's fate is determined by individual success; everyone is responsible for their life; everyone can rise as long as they work hard; social inequality is a problem of person's income which is linear with their hard work; and education is a solution of social inequality; 3) Sandel’s criticism on meritocracy can be an alternative perspective to analyze populism in Indonesia. 4) The challenge of right-wing populism can be answered by revitalizing public discourse. This study concludes that meritocracy is a trigger for the right-wing populism in various democratic countries, including Indonesia.AbstrakArtikel ini bertujuan menganalisis fenomena populisme kanan berdasarkan pemikiran Michael Sandel tentang tirani meritokrasi. Berbagai literatur sebelumnya memahami populisme kanan sebagai gerakan anti-pluralisme dan anti-globalisasi. Namun, analisis-analisis tersebut gagal memahami bahwa meritokrasi telah memicu kemarahan kelas pekerja dan para pecundang yang diekspresikan dalam gerakan populis. Studi ini memakai metode review literatur dan analisis kritis. Studi ini menemukan bahwa: 1) Meritokrasi adalah keyakinan moral tertentu terhadap prestasi individu yang membenarkan ketimpangan sosial sebagai hal yang fair berdasarkan prinsip-prinsip liberalisme; 2) Terdapat lima tesis kunci meritokrasi yaitu: nasib seseorang ditentukan prestasi individu; setiap orang bertanggung jawab atas hidupnya; setiap orang bisa bangkit asalkan bekerja keras; ketimpangan sosial adalah masalah besar-kecilnya penghasilan seseorang yang linear dengan kerja kerasnya; dan pendidikan adalah solusi ketimpangan sosial; 3) Pandangan Sandel dapat menjadi perspektif alternatif untuk membaca populisme di Indonesia. 4) Tantangan populisme kanan dapat dijawab melalui revitalisasi diskursus publik. Studi ini menyimpulkan bahwa meritokrasi merupakan pemicu populisme kanan di berbagai negara demokrasi, termasuk Indonesia.